Tanggung Jawab PT. First Anugerah Karya Wisata First Travel Terhadap Korban - Terrance, John Jotham; Diana Putong; Feibe Engeline Pijoh; Arthur Novy Tuwaidan (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
The fraud case was carried out by First Travel officials Andika Surachman and Anniesa Deavitasari Hasibuan who succeeded in defrauding 63.310 prospective Hajj pilgrims with a total loss of Rp. 905.330.000.000,- who been sentenced to 20 years and 18 years in prison respectively where criminal liability has been imposed on the defendants but civil liability still cannot be borne out even though the panel of judges in the trial for postponing debt payment obligation has agreed to a settlement with peace proposal which contains the debtor's obligation to dispatch the Hajj pilgrims and return money for those who do not wish to depart because first travel's assets no longer exists and first travel is no longer operating